Orchestrating Open Innovation through Punctuated Openness: A process model of open organizing for tackling wicked multi-stakeholder problems. Issue 1 (January 2023) - Diriker, Damla; Porter, Amanda J.; Tuertscher, Philipp
Orchestrating open innovation initiatives characterized by frequent changes in stakeholders and activities can be a daunting task. As these initiatives need to adapt to the constantly changing requirements of the process, they can benefit from an open organizing approach that enables the direct participation of stakeholders, not only in the innovation process but also in its orchestration. Building on the constitutive view on open organizing, we argue that the interactions among various stakeholders can be orchestrated by an open organizing process complemented by elements of closure. However, determining when and how to deploy a closure to complement open organizing remains a practical and theoretical puzzle. We address this puzzle through a longitudinal field study of an award-winning open innovation initiative tackling the sustainability challenges of oceans. We show when and how temporary closures can catalyze the participation of diverse stakeholders across phases, while opening up the organizing process to participatory fine-tuning allows the orchestration to evolve with the changing requirements of the process. By emphasizing the temporal dimension of deploying closure in open organizing, we develop a process model explaining how punctuated openness —open organizing interrupted by moments of closure—can be used as an organizing principle.